Anserine inhibits carnosine degradation but in human serum carnosinase (CN1) is not correlated with histidine dipeptide concentration - Peters, Verena; Jansen, Erwin E. W.; Jakobs, Cornelis; Riedl, Eva; Janssen, Bart; Yard, Benito A.; Wedel, Johannes; Hoffmann, Georg F.; Zschocke, Johannes; Gotthardt, Daniel; Fischer, Christine; Köppel, Hannes (Clinica chimica acta, 2011)
BACKGROUND: We reported an association of a particular allele of the carnosinase (CNDP1 Mannheim) gene with reduced serum carnosinase (CN1) activity and absence of nephropathy in diabetic patients. Carnosine protects against the adverse effects of high glucose levels but serum carnosine concentration was generally low. - METHODS: We measured the concentration of two further histidine dipeptides, anserine and homocarnosine, via HPLC. CN1 activity was measured fluorometically and for concentration we developed a capture ELISA. - RESULTS: We found an association between the CNDP1 Mannheim allele and reduced serum CN1 activity for all three dipeptides but no correlation to serum concentrations although anserine and homocarnosine inhibited carnosinase activity. Patients with liver cirrhosis have low CN1 activity (0.24 ± 0.17 μmol/ml/h, n=7 males; normal range: 3.2 ± 1.1, n=104; p<0.05) and CN1 concentrations (2.3 ± 1.5 μg/ml; normal range: 24.9 ± 8.9, p<0.05) but surprisingly, histidine dipeptide concentrations in serum are not increased compared to controls. - CONCLUSIONS: Serum histidine dipeptide concentrations are not correlated to CN1 activity. The protective effect of low CN1 activity might be related either to turnover of CN1 substrates or a protective function of dipeptides might be localized in other tissues.